Factors Influencing the Interest in a Career as a Public Accountant - Ni Luh Intan Puspita Dewi; I Gst Ayu Eka Damayanthi (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
Career interest describes an individual's interest in a particular field of work that is part of the initial stage of career development. This study aims to obtain empirical evidence regarding the influence of labor market considerations, financial rewards, family environment, professional recognition, professional training on career interest as a public accountant. The sampling method used was snowball sampling. The sample size was 156 respondents and was analyzed using SEM-PLS. Data collection was carried out using a survey method and distributing questionnaires. The results of this study indicate that labor market considerations, financial rewards, family environment, professional recognition, professional training increase career interest as a public accountant. The theoretical implications of this study support the empirically proven hierarchy of needs theory. The results of this study provide practical implications for public offices that labor market considerations, financial rewards, family environment, professional recognition, professional training influence career interest as a public accountant.